THE ROLE OF FOSTER PARENTS IN IMPLEMENTING CHARACTER EDUCATION - Ari Susandi; Izzuddin Ibnu Abdis Salam; Mohammad Arifin (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2021)
The purpose of this research is to describe the role of foster parents in instilling the value of character education. Of course, parents should be more concerned with the child in order to get maximum education, especially at the age of the children. Considering that mothers are the first madrasas for children, they are instead left to work for the reason that they want to improve the family's economy. That way, parents leave their children in the hope of getting maximum care from those who care for them. This study aims to determine the role of foster parents in instilling character education in Puspan Village, Maron District, Probolinggo Regency. The data for the study were collected by selecting by observation, interviews and documentation. The samples were selected using a random technique based on the area or region where the data analysis technique used was by connecting the data with one another and the sample was three families who worked as laborers. Indonesian workforce consisting of three husband and wife couples who leave their children with the family of Mrs. Sunarsih, Mrs. Sum and Mrs. Nur Fadila. Based on data analysis, it was found that the role of foster parents in instilling character education in Puspan Village, Maron District, Probolinggo Regency has been categorized as successful. Because children are able to implement what has been taught by foster parents, they are able to become children's motivators, as facilitators, as guides in instilling the value of religious character education, independence, tolerance in children.